Business Improvement Districts in Deutschland - Kontextualisierung einer "mobile policy" - Pütz, Robert; Stein, Christian; Michel, Boris; Glasze, Georg (Geographische Zeitschrift, 2014)
The introduction of Business Improvement Districts (BJD) in Germany can be seen as an exemplary case of a .mobile policy. As modes of governance that are being implemented throughout multiple national and international contexts, mobile policies offer prime examples for the ways in which urban policies are increasingly produced by translocal networks. BIDs promise to bring private capital and civic commitment to inner cities and to help them compete with suburban shopping centers. In the first part of this article we focus on the question of whether BDZs can be regarded as paradigmatic for new modes of governance in the .entrepreneurial city and whether its globalization can shed light on more general processes of neoliberal urbanism. In the second part we deal with the scope and limits of theoretical approaches that try to understand the global proliferation of policy models. Using the framework of a policy mobilities approach in particular, we draw on case studies on BIDs in Germany. © Franz Steiner Verlag, Stuttgart.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Business Improvement Districts; Entrepreneurial city; Germany; Policy mobilities; Public private partnerships